The Application of Hirschberg Maxims in Frost’s ‘Mending Wall’ and Darwish’s ‘Scenario Jaahiz’: A Phono-Pragmatic Analysis - AL-Badri, Manaar M.A.; Al-Zubaidi, Nassier A. G. (Al-Adab Journal, 2022)
This paper presents a study of prosodic traits and the pragmatic implications connected to them. It is suggested that there is a prosodic code in which a selection of suprasegmental elements is deliberately and consciously changed, putting it in relation to syntactic structures, lexical choices, and pragmatic meanings, is believed that a prosodic grammar works together with the linguistic and rhetorical devices in order to organize a narrative discourse firstly, and secondly to highlight the argumentative part within the narrative discourse. The prosodic features and the possible communicative meanings associated as well as the pragmatic effects are all described and justified. This study is the result of the analysis of two narrative poems in two different languages; English and Arabic. It is believed that the methodological procedures followed and the conclusions arrived at can be easily extended to other languages. General correlations that could be a starting point for further studies and practical employment of prosodic features are proposed.